Fabrication of carboxymethylated cellulose fibers supporting Ag NPs@MOF‐199s nanocatalysts for catalytic reduction of 4‐nitrophenol. (5th March 2019) - Duan, Chao; Liu, Chaoran; Meng, Xin; Lu, Wanli; Ni, Yonghao
Abstract : In this work, we prepared high‐performance and recyclable nanocatalysts that consist of small and well‐dispersed silver nanoparticles (Ag NPs) immobilized onto Cu‐ based metal–organic framework (MOF‐199 s) supported by carboxymethylated cellulose fibers (CCFs). The as‐prepared green nanohybrid catalysts, namely Ag NPs@ MOF‐199 s/CCFs, were characterized using SEM, TEM, XRD and FT‐IR techniques. The catalytic performances showed that Ag NPs@ MOF‐199 s/CCFs catalysts exhibited a very high catalytic efficiency towards the reduction of 4‐nitrophenol to 4‐aminophenol. The enhanced catalytic performances are attributed to the improved dispersity, small particles of Ag NPs stabilized by the MOF‐199 s, and the porous catalyst structures. The introduction of cellulose fiber further facilitates the reuse and sustainability of the nanohybrid catalysts, showing a stable and high reusability (more than 91% of catalytic activity) even after five runs. Abstract : Novel cellulose‐based catalysts, namely Ag NPs@MOF‐199 s/CCFs, exhibited robust catalytic activity and excellent recyclability during the catalytic reduction of 4‐NP. The enhanced catalyticperformance can be attributed to the synergetic effect from the improveddispersity of Ag NPs and the porous MOF‐199 s themselves with high electron transfer, while cellulose fibers can further facilitate the reuse andsustainability of the nanohybrid catalysts.